Penerapan Algoritma C4.5 Dalam Menentukan Prediksi Prestasi Siswa Pada SMPN 51 Jakarta - Muhammad Hamdan Sukri; Yopi Handrianto (Informatics and Computer Engineering Journal, 2024)
The world of education is the birthplace of state servants and the instrument for forming the personality of the state. Schools are the most important places where Indonesia's "state builders" must strive to bring this country to world competition. This study aims to apply the C4.5 algorithm in determining student achievement predictions at SMPN 51 Jakarta. The method used in this study is the C4.5 algorithm, which is one of the most popular and effective machine learning algorithms for decision making. Algorithm C4.5 is used to build a predictive model of student achievement based on various relevant attributes, such as attendance, attitude scores, and extracurriculars. the results of the implementation are carried out using the Data Mining Rapid Miner software, where the results will later prove that the results of the analysis carried out by applying the C4.5 algorithm are in accordance with the results of the implementation. The results obtained are the "Extra Curricular" attributes which become leaves or leaves. Then the attribute "Alpha" gets the highest gain value with a result of 1. Then "Alpha" becomes the last B root node. Then the attribute "Alpha" SB becomes the last root node that gets the highest gain value with a result of 0.468995594. Then the attribute "Alpha" with a value > 0 has an unachieved answer or "NO" and with a value <= 0 has an achievement answer.